Discontinuation of Denosumab and Associated Fracture Incidence: Analysis From the Fracture Reduction Evaluation of Denosumab in Osteoporosis Every 6 Months (FREEDOM) Trial - Brown, Jacques P (Wiley Subscription Services, Inc., A Wiley Company, 2013)
Osteoporosis is a chronic disease and requires long-term treatment with pharmacologic therapy to ensure sustained antifracture benefit. Denosumab reduced the risk for new vertebral, nonvertebral, and hip fractures over 36 months in the Fracture Reduction Evaluation of Denosumab in Osteoporosis Every 6 Months (FREEDOM) trial. Whereas discontinuation of denosumab has been associated with transient increases in bone remodeling and declines in bone mineral density (BMD), the effect on fracture risk during treatment cessation is not as well characterized. To understand the fracture incidence between treatment groups after cessation of investigational product, we evaluated subjects in FREEDOM who discontinued treatment after receiving two to five doses of denosumab or placebo, and continued study participation for ≥7 months. The off-treatment observation period for each individual subject began 7 months after the last dose and lasted until the end of the study. This subgroup of 797 subjects (470 placebo, 327 denosumab), who were evaluable during the off-treatment period, showed similar baseline characteristics for age, prevalent fracture, and lumbar spine and total hip BMD T-scores. During treatment, more placebo-treated subjects as compared with denosumab-treated subjects sustained a fracture and had significant decreases in BMD. During the off-treatment period (median 0.8 years per subject), 42% versus 28% of placebo- and denosumab-treated subjects, respectively, initiated other therapy. Following discontinuation, similar percentages of subjects in both groups sustained a new fracture (9% placebo, 7% denosumab), resulting in a fracture rate per 100 subject-years of 13.5 for placebo and 9.7 for denosumab (hazard ratio [HR] 0.82; 95% confidence interval [CI], 0.49–1.38), adjusted for age and total hip BMD T-score at baseline. There was no apparent difference in fracture occurrence pattern between the groups during the off-treatment period. In summary, there does not appear to be an excess in fracture risk after treatment cessation with denosumab compared with placebo during the off-treatment period for up to 24 months. © 2013 American Society for Bone and Mineral Research.